Nursing Students’ Stress in Clinical Practice: A Grounded Theory Study. - dos Santos, Sara Soares; Silva, Ítalo Rodolfo; Araújo, Agostinho Antônio Cruz; de Godoy, Simone; Gardim, Lucas; de Almeida, Emerson Willian Santos; Gastmans, Chris; Mendes, Isabel Amélia Costa (Investigación & Educación en Enfermería)
Objective. To explore nursing students’ perspectives on stress in clinical practice, focusing on causal conditions, intervening factors, and related consequences. Methods. This is a qualitative study conducted using grounded theory, following the Straussian perspective. Fifteen undergraduate nursing students enrolled in clinical training in two programs at a public university in southeastern Brazil. Semi-structured individual interviews were analyzed through open, axial, and selective coding. Informed consent forms were obtained from all participants. Results. Stress in clinical practice was perceived as a multifactorial and dynamic phenomenon, triggered by difficulties in adapting to the clinical environment, academic overload, interpersonal conflicts, and strained relationships with educators and preceptors. These causal and intervening factors produced persistent biopsychosocial consequences, including physical symptoms, emotional instability, cognitive impairments, diminished selfconfidence, and concerns about patient safety. Students emphasized that inadequate support, disrespectful interactions, and humiliating behaviors contradicted ethical expectations for safe, respectful, and inclusive learning environments, thereby intensifying moral distress and compromising learning. Conclusion. Stress arising from clinical practice is influenced by pedagogical, relational, and ethical dimensions. Creating ethically grounded clinical learning environments requires recognizing that student well-being is inseparable from the moral climate of teaching and supervision. Institutions and educators hold pedagogical, political, and ethical responsibilities to implement strategies that support student adaptation, safeguard well-being, and strengthen the quality of clinical education.